Higher Education Students and Covid-19: Challenges and Strategies in facing Online Learning - Fathoni, Anang; Mustadi, Ali; Kurniawati, Wahyu (Jurnal Pendidikan Indonesia, 2021)
The emergence of Covid-19 has had a significant influence on the world of education. Even though the emergence of Covid-19 has accelerated the integration of technology in learning, there are still negative classroom learning impacts. This study aims to explore student experience in online learning in the Covid-19 Pandemic period; describe the negative impacts and obstacles that arise in online learning; and describe student strategies in online learning. This research is qualitative in the type of case studies. Data were collected through open questionnaires and interviews with participants of 20 students. Data analysis was accomplished with Bogdan and Biklen models through reduction, searching for sub-themes, and seeking relationships between sub-themes to obtain the conclusion. The results of this study show that learning in the Covid-19 pandemic period has not been fully optimally done. In addition, students also get physical and mental impacts during online learning. Furthermore, students get barriers to signals, learning environment, and learning activities with lecturers online. However, students have a varied learning strategy to minimize obstacles and negative impacts of online learning.